PERSEPSI GURU TERHADAP PELAKSANAAN TUGAS KEPALA SEKOLAH DALAM BIDANG ADMINISTRASI DI SDN KECAMATAN LEMBAH SEGAR KOTA SAWAHLUNTO - Gusti Rahayu (Jurnal Bahana Manajemen Pendidikan, 2013)
Based on observations and interviews obtained the following information. School head teachers in implementing the lack of attention to learning in the school, the principal was not trying to improve the ability of school personnel, especially teachers, principals less provide oversight of the implementation of the duties of teachers, so there is still a lack of discipline teachers in performing their duties, making the school's annual report often delayed and late given to the District Office. The purpose of this study is the teacher's perception of the performance of duties as a Principal Administrator in administering the program and student at SDN PBM District Jenis penelitian bersifat deskriptif. The population in this study were all public elementary school teachers in the District Lembah Segar Kota Sawahlunto which totaled 110. Random sampling technique purpose beside the number of samples as many as 52 people. Using questionnaire data collection techniques and data analysis techniques using a percentage formula. The results portray that Teacher Perceptions Toward Implementation of the School Governors for Administration as follows: Perception of Teachers on the implementation of the principal tasks in the field of school administration views of fields including category PBM quite to the level of achievement of 76.6%. Teacher perception of the implementation of the principal tasks in the field of school administration views of fields including categories of student achievement enough to level 74.0. Keywords: Implementation of the task, the administration